Water smart technologies for enhancing productivity, profitability and energy use efficiency of taro (Colocasia esculenta) - SUNITHA, S; KUMAR, J SURESH; RAMESH, V; SUJA, G (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2019–2020 and 2020–2021 at ICAR-Central Tuber Crops Research Institute, Thiruvananthapuram, Kerala to compare the effects of different irrigation water saving techniques on productivity, water use efficiency, energy use efficiency and profitability of taro [Colocasia esculenta (L.) Schott]. The improved variety of taro, ’Muktakeshi’ was used in the experiment under randomized block design (RBD). The crop was raised under upland conditions with drip irrigation and irrigated at the rate of 50% crop evapotranspiration (ETc) along with water saving treatments, viz. mulching using porous ground cover mat (T1), bio-mulching (T2), coir pith mulching (T3), anti-transpirant spray on foliage (T4), soil application of pusa hydrogel (T5) and synthetic super absorbent polymer (T6). Drip irrigation at 100% ETc and furrow irrigation were kept for comparison. Drip irrigation at 50% ETc along with mulching using porous ground cover mat resulted in highest taro cormel yield, which was 32.2% higher than irrigation at 100% ETc. Use of porous ground cover mat also recorded 60% increase in water productivity, 20% higher energy use efficiency, 37% higher energy productivity and 37% increase in net income, in addition to saving in 50% irrigation water. Drip irrigation at 50% ETc with ground cover mat also recorded 63.8% increase in cormel yield, 3.8 times the water productivity and 100% saving in irrigation water, compared to furrow irrigation. Taro, being a highly water sensitive crop, suitable water saving measures are necessary to ensure its sustainable yield per drop of water, especially in the era of climate change. The results suggested the suitability of porous ground cover mat as a water smart technology for upland taro production in the tropical regions.